Enterprise competitiveness management in modern business conditions - Savenko, V.; Nesterenko, I.; Klyuyeva, V. (Ways to Improve Construction Efficiency, 2019)
The need to manage the competitiveness of the enterprise is due, first of all, to the ongoing rapid changes in the environment, the emergence of unpredictable economic and financial situations. An effective enterprise competitiveness management system ensures the firm's stable position on the market, creating a steady increase in its competitive advantages in a rapidly changing environment. The analysis of the literature has shown that the competitiveness of the enterprise in the general classification of management objects can be attributed to functional (as opposed to production and structural), which require the development of a special management mechanism. The main task is to theoretically substantiate and develop the basics of methodological support for the formation of a strategic management system for the competitiveness of construction enterprises, which will allow to achieve, on the one hand, competitive advantages in the form of low cost enterprise, and on the other - more effective implementation of construction projects on the basis of optimization of management and construction financing - assembly works. The article considers the basic elements of managing the competitiveness of the enterprise and products, the competitiveness indicators of the construction company, the principles of choosing basic competitive strategies, taking into account the real capabilities of the enterprise. The role of the main determinants of internal and external factors that influence the effective activity of a production organization and their importance for enhancing the competitiveness of a construction company, as well as the ability to manage competitiveness in market relations are shown. It is revealed that the enterprise competition strategy is more than just the sum of the strategies of individual units, and one of the basic factors for the competitiveness of construction products is the time of construction of the building and its commissioning. The connection between the competitiveness of the enterprise and the competitiveness of construction products is identified, and the factors that shape it are determined.